Evaluating Indonesia's Renewable Energy Transition Strategy: Policy Implementation Challenges Toward Net-Zero Emission Target 2060 - Kurniawan, Okta Dwi Andika; Sari, Diah Permata; Wulandari, Christine; Bakri, Samsul; Febriyano, Indra Gumay (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
Indonesia, as the world's largest archipelagic nation, faces complex challenges in achieving its net-zero emission target by 2060. This research analyzes the implementation of Indonesia's new and renewable energy (NRE) policies through a comprehensive literature study approach. Despite having strong legal foundations through Law No. 30/2007 and Government Regulation No. 79/2014, along with ambitious targets of 23% renewable energy by 2025, implementation realization still encounters significant obstacles. National Energy Council data shows that renewable energy share has only reached 15%, far from the established targets. Analysis of three projection scenarios from the Ministry of Energy and Mineral Resources - Business as Usual (BaU), Sustainable Development (SD), and Low Carbon (LC) - indicates that the SD scenario can achieve the 23% target by 2025 and even exceed the 31% target by 2050. Research findings demonstrate that although Indonesia possesses abundant renewable energy resource potential and clear political commitment, strengthening law enforcement, infrastructure investment, and inter-stakeholder coordination are required to realize sustainable energy transition toward net-zero emission.